A Word on Words in Words: How Do Embedded Words Affect Reading?. Issue 1 (25th September 2018) - Snell, Joshua; Grainger, Jonathan; Declerck, Mathieu
A surprisingly small portion of reading research has been dedicated to investigating how the visual word recognition process is influenced by embedded words (e.g., ' arm ' in ' charm '), and no research has yet investigated embedded words in a natural reading setting. Covering this issue, the present work reports analyses of eye-tracking data from the GECO bilingual book reading corpus. Word viewing times were analyzed as a function of the number, frequency and proportional length of embedded words. We anticipated two scenarios: embedded words would either facilitate processing due to increased word-letter feedback, or inhibit processing due to increased lexical competition. A main facilitatory effect of embedded words on the recognition process was established, with an increasing number of embedded words resulting in shorter word viewing times and fewer fixations. This pattern was depicted by readers of Dutch as well as readers of English. Long, high-frequency embedded words formed an exception however, as these led to inhibition (Dutch participants) or a null-effect (English participants). The present results indicate that both scenarios outlined above are at play, but with a theoretical constraint on the role of word-to-word inhibitory connections. Specifically, such connections may predominantly exist among words of similar length. Hence, embedded words generally facilitate processing through word-letter feedback, but this facilitatory effect is countered by word-to-word inhibition if the embedded word's length approximates that of its superset.